Modern Management Accounting Practices for Large Manufacturing Enterprise in Lower Northern Provinces Group I Thailand - Suranatthakul, Kanogporn; Dokmaithong, Supaporn; Intanon, Ruankwan; Phetruen, Warawit; Sumkaew, Nuatip (Journal of Accounting, Business and Finance Research, 2020)
The rapidly increasing global and technological changes have given rise to the need of changing enterprise management. Therefore, modern management accounting practices (MAPs) are important for the enterprise and its manager to support the decision-making process, improve management activity, and help the operation effectively. Generally, the larger the organization, the greater the management's need for information. This work studies the modern MAPs that the enterprise applies, including barriers to the adoption. A descriptive study was performed in 10 large manufacturing enterprises in the lower northern provinces group I Thailand. Structured questionnaires and in-depth qualitative interviews with manager/ owner show that most large manufacturing enterprises are low level to apply for modern MAPs. Most large manufacturing enterprises prefer to use part of target costing, balanced scorecard, quality cost, and environmental management. All firms do not implement activity-based management and product life cycle costing. A few firms used the theory of constraint and just-in-time. Although those modern MAPs have not been fully applied and some modern MAPs are rarely or never used, managers are trying to apply modern MAPs slowly. However, the study also indicated that the managers have moderate satisfaction on current modern MAPs for decision making. Moreover, this study revealed that the key barriers limiting the implementation of modern MAPs were lack of employee skills/ training/ consultant about modern practices, high cost to implement, and no significant problems with current practices, respectively.